A Positive Relationship Between Sign Language Comprehension and Mental Rotation Abilities. (26th September 2020) - Kubicek, Emily; Quandt, Lorna C
Abstract: Past work investigating spatial cognition suggests better mental rotation abilities for those who are fluent in a signed language. However, no prior work has assessed whether fluency is needed to achieve this performance benefit or what it may look like on the neurobiological level. We conducted an electroencephalography experiment and assessed accuracy on a classic mental rotation task given to deaf fluent signers, hearing fluent signers, hearing non-fluent signers, and hearing non-signers. Two of the main findings of the study are as follows: (1) Sign language comprehension and mental rotation abilities are positively correlated and (2) Behavioral performance differences between signers and non-signers are not clearly reflected in brain activity typically associated with mental rotation. In addition, we propose that the robust impact sign language appears to have on mental rotation abilities strongly suggests that "sign language use" should be added to future measures of spatial experiences.